Determinant Analysis of the Manufacturing Industry Sector’s on Labor Absorption in Sidoarjo and Pasuruan Districts - Rizka Widya Maharani; Riko Setya Wijaya; Putra Perdana (Universitas KH. Abdul Chalim Mojokerto, 2025)
The phenomenon of suboptimal labor absorption in Sidoarjo and Pasuruan districts as the industrial base areas of East Java Province has led to an increase in unemployment problems in both districts. To maximize the potential of existing industries to absorb more labor, it is necessary to analyze the influence of industrial sector factors on the absorption of industrial sector labor in Sidoarjo and Pasuruan districts. This research method uses a quantitative descriptive approach. The type of data used is time series data from 2010-2023. The data analysis technique used is multiple linear regression model analysis using classical assumption test. The results of data analysis found that Industrial GRDP and HDI have a positive and significant effect on employment in Sidoarjo and Pasuruan districts. Meanwhile, the number of industries and industrial investment have no significant and positive effect on employment in Sidoarjo and Pasuruan districts. Furthermore, the minimum wage has a significant and negative effect on employment in Sidoarjo and Pasuruan districts.